2020
DOI: 10.1097/md.0000000000020324
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of recurrence after resection of well-differentiated non-functioning pancreatic neuroendocrine tumors

Abstract: Although pancreatic neuroendocrine tumors (PNETs) are generally considered to have a favorable overall prognosis after resection, disease recurrence has been observed. Few studies have specifically addressed recurrence after resection of PNETs, especially for non-functioning PNETs (NF-PNETs). The aim of our study is to analyze the recurrence of resected well-differentiated NF-PNETs. Patients who underwent surgical resection for grade 1 and 2 NF-PNETs without synchronous metastasis were identified f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
5
9
0
Order By: Relevance
“…Among patients who had received surgical resection, the long-term prognosis between blacks and whites were not significant difference in this study, and white people had worse OS/CSS than that of other race such as Asian American. Many studies suggested that preoperative lymph node metastasis was associated with the long-term prognosis in pNET patients [ 18 , 19 ], while others have not found a significant connection [ 20 , 21 ]. In this study, Cox multivariate analysis suggested that lymph node metastasis could not be used as an independent prognostic factor for postoperative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients who had received surgical resection, the long-term prognosis between blacks and whites were not significant difference in this study, and white people had worse OS/CSS than that of other race such as Asian American. Many studies suggested that preoperative lymph node metastasis was associated with the long-term prognosis in pNET patients [ 18 , 19 ], while others have not found a significant connection [ 20 , 21 ]. In this study, Cox multivariate analysis suggested that lymph node metastasis could not be used as an independent prognostic factor for postoperative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors for poor prognosis, including pathological tumour size, margin status, tumour grade, Ki-67 index, perineural invasion, microvascular invasion, and LNM, have been previously reported in patients with NF-PNENs after curative surgery [7][8][9][10][11]13]. However, in this study, multivariate analysis showed that only the presence of LNM was independently associated with poor OS and DFS in patients with NF-PNENs.…”
Section: Discussionmentioning
confidence: 52%
“…Several previous studies have also reported that LNM is independently associated with poor prognosis in patients with PNENs [12,13,18]. Tan et al investigated the predictors of recurrence in 88 patients with well-differentiated NF-PNENs after curative surgery and found that the presence of LNM was most strongly associated with recurrence, and patients with LNM developed recurrence seven times more often than those without it [13]. In addition, Fischer et al investigated the predictors of poor OS in 291 patients with PNENs after surgical resection [18].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Among patients who had received surgical resection, the long-term prognosis between blacks and whites were not signi cant difference in this study, and white people had worse OS/CSS than that of other race such as Asian American. Many studies suggested that preoperative lymph node metastasis is associated with the long-term prognosis in pNET patients [19,20], while others have not found a signi cant connection [21,22]. In this study, Cox multivariate analysis suggested that lymph node metastasis could not be used as an independent prognostic factor for postoperative patients.…”
Section: Discussionmentioning
confidence: 53%